Are friends of schools the enemies of equity? The interplay of public school funding policies and private external fundraising - Lisa Barrow; Sarah Komisarow; Lauren Sartain (Federal Reserve Bank of Chicago, 2023)
School districts across the U.S. have adopted funding policies designed to distribute resources more equitably across schools. However, schools are also increasing external fundraising efforts to supplement district budget allocations. We document the interaction between funding policies and fundraising efforts in Chicago Public Schools (CPS). We find that adoption of a weighted-student funding policy successfully reallocated more dollars to schools with high shares of students eligible for free/reduced-price (FRL) lunch, creating a policy-induced per-pupil expenditure gap. Further, almost all schools raised external funds over the study period with most dollars raised concentrated in schools serving relatively affluent populations. We estimate that external fundraising offset the policy-induced perpupil expenditure gap between schools enrolling the lowest and highest shares of FRL-eligible students by 26-39 percent. Other districts have attempted to reallocate fundraised dollars to all schools; such a policy in CPS would have little impact on most schools' budgets.
Keywords: I22; I28; H75; 330; education finance; public school; school funding; non-profits; fundraising; equity